Renal glomerular and tubular injury in the offspring of the preeclampsia-like syndrome - Yong Wang; Hao Wang; Huiqing Lu; Ji Ma; Wei Wu; Yinan Wang; Bo Ma; Hao Zhu; Rong Hu (Scientific Reports)
Abstract Preeclampsia (PE) is a prevalent and severe pregnancy complication that significantly impacts maternal and perinatal health. Epidemiological studies and animal experiments have demonstrated that PE adversely affects the cardiovascular and nervous systems of offspring, increasing their risk of hypertension and renal pathology. However, the mechanisms underlying this increased risk remain unclear. This study utilized an L-NAME-induced preeclampsia mouse model (PELS model) to investigate the effects of PE on offspring blood pressure and renal pathology, focusing on the expression of Angiotensin II Type 1 Receptors (AT1R) and related molecules in renal tissues. Our findings show that L-NAME-induced pre-eclampsia led to reduced birth weights and significantly elevated systolic blood pressure in 6-week-old offspring. Histopathological analysis revealed pronounced glomerular and tubular damage in the kidneys of both 1-week and 6-week-old offspring from the pre-eclampsia group. At 1 week of age, the pre-eclampsia group exhibited elevated mRNA and protein expression levels of AT1R, GRK4, AQP2, ENaC, and NCC in renal tissues compared to controls. However, these differences were no longer significant at 6 weeks of age. No significant gender differences were observed in either blood pressure or renal pathological changes. Preeclampsia induced by L-NAME results in increased blood pressure and renal damage in offspring, potentially mediated by early alterations in the renal RAS system. The observed changes in AT1R and related molecules appear to be transient, suggesting that the early impact of pre-eclampsia on renal structure may trigger, but not sustain, hypertension in offspring. Further studies are needed to elucidate the long-term mechanisms driving hypertension in this population.